Katie's forever promise [large type] - Eicher, Jerry S. (Eicher, Jerry S. Emma Raber's daughter, 2014)
In book 3 of the Emma Raber's Daughter series, Amish fiction author Jerry Eicher brings the faith-filled journey of Katie Raber to its happy conclusion. Katie Raber is trying to put her life back together after Ben Stoll's devastating betrayal of her love. When she is baptized into the church, she receives a surprising offer that will keep her close to her Amish community--much to her mother's delight. But soon Ben is back in her life again--and at the same time she finds interest from another young man, though his bumbling efforts at winning her heart show him to be a far less desirable suitor than the more polished Ben Stoll.